Quality by Design (QbD) application for the pharmaceutical development process - Lee, Sang Ho; Kim, Jin Ki; Jee, Jun Pil; Jang, Dong Jin; Park, Young Joon; Kim, Joo Eun (Journal of Pharmaceutical Investigation, 2022)
Background: Quality by Design (QbD) is a pharmaceutical quality management system that predicts, controls, and systematically responds to risks that may occur in the research stage and manufacturing process. There are many articles on how to improve quality through application of the QbD system, but the methodology surrounding how to specifically apply this process is limited. The purpose of this review was to provide accurate information on drug development process and overcome the difficulties of developing QbD-applied drug products through an appropriate application method. Area covered: QbD-based pharmaceuticals are continuously being developed worldwide, helping to identify potential risks, and managing all aspects, from drug design to patient consumption, further enabling the patient to be administered a high-quality drugs based on their design. In this study, a basic knowledge of QbD, its application and effectiveness during drug development will be discussed. Expert opinion: Our results suggest that a QbD for drug development can reduce risk to patients, improve drug quality, and continuously produce superior quality drug products.
Keywords: CMAs; CPPs; CQAs; Pharmaceutical development process; QTPP; Quality by Design